Acute anodal transcranial direct current stimulation improves the performance of professional rowers - Ramos, Luciano; Ramos, Tatiana Aparecida Magacho; Almeida, Rodrigo Freire De; Silva-Rocha, Jader Vinicius da; Zimerer, Carla; Arêas, Fernando Zanela (Frontiers in Sports and Active Living, 2024)
This study aims to evaluate the influence of acute Transcranial Direct Current Stimulation (tDCS) on physical and subjective responses in professional rowing during the 2000-m time trial Test. Seven rowers (20,86 ± 4,49y; 71,66 ± 7,97kg) participated in this randomized triple-blind trial with a crossover experimental design. The protocol consists of two days with different conditions (Anodal and Sham).The tDCS anodic stimulation conducted was 2mA for 20 minutes in the left temporal cortex (2,5cm from the F7 zone and 2,5cm to the T3 zone), targeting the left insular cortex (LIC). In Sham moment, the participants suffered 30 seconds of stimulation. Afterward, they performed a standardized progressive warm-up for 15 minutes, following the Brazilian Rowing Confederation's assessment protocols, and rested for 3 minutes before the Test started. All procedures were made in an indoor rowing machine, which allowed the capture of performance variables such as TIME performed, POWER in watts (W), PACE (meters/min), and STROKE RATE (stroke per minute). The Ratings of Perceived Exertion (RPE) (Borg scale [CR-20]) were caught in 2 by 2-min during the Test. The results presented differences in POWER (Z: -2,371; p = 0,018; ES = -0,896 [large]) and PACE (Z: -2,371; p = 0,018; ES = -0,896 [large]) and TIME performance (Z: -1,612; p = 0,107; ES = -0,609 [large])throughout the protocol for the Anodal moment. However, no differences for the other variables were found. According to the results, the current tDCS assemble stimulation and protocol improved the physical performance at the 2000-m time trial Test providing ergogenic aid.